MANAGEMENT OF PALATAL EXTERNAL CERVICAL ROOT RESORPTION (Journal of Medical & Health Sciences Review, 2025)
A 24-year-old female patient presented to the Department of Operative Dentistry at the International Islamic Dental Hospital with a chief complaint of slight discomfort in the upper anterior region and she also felt that the tooth was slightly discoloredHistory of the patient revealed that 1 year ago she fell from her bed and felt pain in the anterior teeth for 3 to 4 days which settled down on its own.  The clinical examination showed #11 was discolored and mildly tender to percussion.Cold test gave no response on #11 and radiograph showed a large radiolucency in the cervical area which was approximately extending till the middle third of the root.The periodontal pocket depth on the palatal side was 6 mm and also bleeding on probingCBCT was taken to assess the lesion. A diagnosis of external cervical resoprtion was made. Patient made well aware of the prognosis of the tooth.Non-surgical root canal treatment followed by surgical repair of the defect was carried out and an extra coronal restoration was given.